PEMILIHAN PEMASOK MENGGUNAKAN METODE K-MEANS KLUSTERING BERBASIS PYTHON - Zaen, Miftakhul; Boru Butar Butar, Maulida; Nasution, Syarifuddin; Mohamad Noor, Asep (JISI: Jurnal Integrasi Sistem Industri, 2025)
Supplier selection is a decision-making process that is complex and carries a lot of risks. Therefore, in order to make decisions more precise, decision-making requires tools that are scientific, logical and structured. Currently, most supplier selection is done using manual calculations, so it requires accuracy in doing so. With current technological advances supplier selection can be implemented with artificial intelligence. Implementing artificial intelligence by selecting suppliers can reduce errors in manual calculations and hopefully get better suppliers. The purpose of this research is to implement artificial intelligence into supplier selection with the method used, namely K-means clustering with the criteria used are quality, price, and delivery time. The data used in this research is secondary data sourced from Kaggle so the weight of each criterion is unknown. The results of this study show that the best suppliers are supplier 19 in cluster 0, supplier 8 in cluster 1, and supplier 20 in cluster 3.